Islam in Bangladesh: The Legacy of Hazrat Shah Jalal and the Spread of Islam in Bengal - Mahmudulhassan; Muthoifin; Nirwana, Andri; Waston; Abuzar, Muhammad (Journal of Al-Tamaddun, 2025)
This study examines the influential role of Hazrat Shah Jalal, a renowned Sufi saint, in the spread of Islam in Bengal, particularly in present-day Bangladesh. By applying the diffusion of religious ideas theory, this research explores how his missionary approach rooted in cultural adaptation, moral integrity, and spiritual guidance, facilitated the peaceful propagation of Islam. Utilising historical analysis, the study critically examines archival records, including manuscripts, inscriptions, historical chronicles, and colonial documents, to assess Shah Jalal’s contributions. The findings reveal that his teachings significantly shaped Bengal’s religious and cultural landscape by influencing local customs, integrating Islamic traditions, and fostering educational advancements. His disciples played a pivotal role in continuing his mission, establishing Islamic centres, and promoting Islamic scholarship, which contributed to Bengal’s emergence as a centre for Islamic learning. The study underscores the lasting sociopolitical impact of Shah Jalal’s teachings, which helped shape the region’s Islamic identity. By addressing gaps in existing scholarship, this research enhances understanding of the historical roots of Islam in Bengal and provides valuable insights into religious diffusion, cultural integration, and historical sociology.